Strengthening Cooperative Capacity Through Business Feasibility Studies as a Strategy for Sustainable Agribusiness Development - Fildza Arief Syuhada; Andi Alatas; Roni Jarlis; Juli Supriyanti; Taufiqqurrahman Taufiqqurrahman; Vivi Hendrita (Pelita Eksakta, 2026)
This community service aimed to strengthen the capacity of Al-Barkah Mandiri Bersama Cooperative in Nagari Palaluar, Sijunjung, through training and mentoring on business feasibility studies for goat farming. Activities included socialization, discussions, technical training, technology application, and continuous mentoring covering market, financial, management, legal, and risk aspects. Evaluation using pre- and post-tests showed an increase in participants’ understanding from 46% to 71%, with an average normalized gain of 0.63 (medium category). These results indicate that the program effectively improved members’ knowledge and skills in preparing feasibility studies and raised awareness of their importance for sustainable agribusiness. The initiative contributes to cooperative empowerment and local agribusiness development while highlighting the need for follow-up support in financial recording and technical goat farming management to achieve more professional and competitive cooperative operations.